Metaphysical themes in Thomas Aquinas III - Wippel, John F. (Studies in philosophy and the history of philosophy, 2021)
"The third collection of Msgr. Wippel's essays on the metaphysical thought of Thomas Aquinas, covering topics such as the discovery of metaphysics by a special form of judgment, the relationship between faith and reason in the preambles of faith, the distinction between essence and "esse," and participation"--